Effects of Oregano Essential Oil Dietary Supplementation on the Feeding and Drinking Behaviour as Well as the Activity of Broilers - Symeon, George K.; Zintilas, Costantinos; Demiris, Nikolaos; Bizelis, Iosif A.; Deligeorgis, Stelios G. (International Journal of Poultry Science, 2010)
The objective of this study was to evaluate the effect of oregano essential oil dietary supplementation on the feeding and drinking behaviour as well as the activity of broilers. One hundred and twenty female Redbro chicks were randomly assigned to three treatments: Controls, R1 and R2 with 0, 100 and 250 mg oregano essential oil added per Kg of feed, respectively. Their feeding behaviour was recorded from 35-63 days of age. The probabilities of a bird feeding, drinking and moving were significantly decreased by the oregano essential oil supplementation with the higher inclusion level having the greater effect. The age of the chicks and the time of day both had a small but significant negative effect on the visits to the feeder, drinker and the activity of broilers. There was a fairly high positive correlation between the probability of a chicken feeding and drinking and a smaller but still significant correlation between feeding and moving. Oregano essential oil significantly altered feeding behaviour of female broilers with the inclusion level being a significant factor of this change.